Flyers’ Gratification Towards Rajiv Gandhi International Airport - Kumar, A. Arun; Kumar, D. Kiran; Shekhar, V. (Indian Journal of Marketing, 2019)
Air travel has become the most considered mode of transportation being preferred by people today owing to the convenience, comfort, reduced time of travel, and cheaper air fares. The facilities available with the airports have become a matter of concern for the air travellers. In the present paper, we reported the findings of the study conducted to assess the gratification levels of flyers about the facilities and services available at one of the busiest airports in India, Rajiv Gandhi International Airport (RGIA) located in Hyderabad. The questionnaire survey method comprising of 23 questions with a 5 - point Likert scale was adopted by us for the present study. The survey was conducted at the airport, and the questionnaires were collected from passengers who had travelled from different airports. The data obtained from the survey was analyzed using PAF method and CFA model. Five factors which represented 63.8% of the total variance of the original variables were extracted. The five factors are : Economize Time, Palpable Facilities, Cordial Services, Ease of Travelling, and Ambience of the Terminal, which formed the paramount framework of flyers’ gratification. The results of the study revealed that flyers’ satisfaction levels were based on both the services as well as facilities which were found to be highly correlated to each other.